(untitled) (Ingeniería y Desarrollo, 2011)
Este trabajo muestra la metodología para determinar el comportamiento a fractura en un acero sinterizado. Se ha evaluado la tenacidad a fractura y la porosidad en un acero sinterizado de composición química Fe-4.0Ni-1.5Cu-0.5Mo-0.5C en el rango de densidad de 7.20 a 7.51 g/cm3. Los niveles más altos de densidad se alcanzaron por medio de la doble compactación y sinterización de polvos precalentados. Los resultados muestran un incremento en la tenacidad de fractura con la densidad debido al aumento de la esfericidad de los poros, la reducción del tamaño medio de éstos y su mejor distribución. A pesar de utilizar tres tipos de lubricantes diferentes para la compactación del polvo, los resultados sólo dependen del nivel de densidad de sinterizado. / This paper shows the methodology to assess fracture behaviour in sintered steels. Fracture toughness and the microstructure of PM steel (Fe-4.0Ni-1.5Cu-0.5Mo- 0.5C) have been studied as a function of sintered density in a range from 7.20 to 7.51 g/cm3. Highest densities were achieved by warm compaction and double pressing- double sintering using three different lubricants. A quantitative analysis of microstructure was correlated with fracture behavior to assess the influence of pore morphology on mechanical properties. Fracture toughness increased with density, being this performance a remarkable advantage over wrought steels. Results showed that the enhanced behavior of the denser samples is due to improved distribution of more spherical porosity. In spite of using different lubricants, the final results depend solely on sintered density reached by each processing route.